Immobilized endo-xylanase of Aspergillus tamarii Kita: an interesting biological tool for production of xylooligosaccharides at high temperatures. (February 2017) - Heinen, P.R.; Pereira, M.G.; Rechia, C.G.V.; Almeida, P.Z.; Monteiro, L.M.O.; Pasin, T.M.; Messias, J.M.; Cereia, M.; Kadowaki, M.K.; Jorge, J.A.; Polizeli, M.L.T.M.
Graphical abstract: Highlights: An endo -xylanase from Aspergillus tamarii Kita was purified using CM-cellulose. The derivative glyoxyl-agarose demonstrated an important hiperactivation (2.4-fold). There was an increased thermostability of the enzyme upon multipoint immobilization. The immobilization of xylanase enabled to successfully produce xylooligosaccharides. Abstract: An endo -xylanase produced by Aspergillus tamarii Kita was purified using the support CM-cellulose. The enzyme was immobilized on CM-cellulose, glyoxyl-agarose and CNBr-agarose, but the best support was considered the glyoxyl-agarose since its derivative had more stability than the CNBr-agarose derivative (control) in broad range of temperature. The derivatives had an important hyperactivation on glyoxyl-agarose (2.4-fold) and CM-cellulose (5.1-fold). The immobilization of the enzyme improved the physicochemical parameters, since increased enzyme optimum temperature in 5 degrees, which changed from 60 °C in the control to 65 °C after multipoint covalent immobilization. Thermostability of the glyoxyl-agarose derivative showed half-life (t0.5 ) values of 96 and 60 min at 70 and 80 °C, respectively. Both derivatives showed apparent optimum pH of 5.5. Glyoxyl-agarose derivative was used in 5 consecutive cycles, maintaining more than 80% of its residual activity. The immobilization of endo -xylanase showed to be a very useful method for improving thermostability up to 80 °C and enabled to successfully produce xylooligosaccharides (XOS) of 2–5 degree of polymerization (DP 2–5), especially xylotriose (39.7%) and xylotetraose (29.4%), at high temperatures. The glyoxyl-agarose derivative is a potential resource to numerous biotechnological processes, especially in large scale production of XOS which could be used as prebiotic supplementation.